Comparison and Analysis of Magnetizing Inrush and Fault Condition for Power Transformer - Banerjee, Mudita; Anita Khosla, Dr. (International Journal of Engineering and Technology, 2018)
This paper presents the second harmonics present in the primary current of a power transformer at different conditions using Fast Fourier Transform and Total Harmonic Distortion techniques to analyze the inrush condition and to distinguish it with fault condition of a power transformer. Result shows that the 2nd harmonic content is pre-dominant in inrush condition of primary current of the power transformer. It is observed that there are significant differences amongst the parameters found during inrush condition, normal condition and internal fault condition which are useful in the identification of magnetizing inrush current of power transformer. The simulation is done in MATLAB/SIMULINK.Â